Investor Sentiment and the Closed-End Fund Puzzle. - Lee, Charles M C; Shleifer, Andrei; Thaler, Richard H (Journal of Finance, 1991)
This paper examines the proposition that fluctuations in discounts of closed-end funds are driven by changes in individual investor sentiment. The theory implies that discounts on various funds move together, that new funds get started when seasoned funds sell at a premium or a small discount, and that discounts are correlated with prices of other securities affected by the same investor sentiment. The evidence supports these predictions. In particular, the authors find that both closed-end funds and small stocks tend to be held by individual investors, and that the discounts on closed-end funds narrow when small stocks do well.